Faktor Penghambat Bantuan Asing The Global Fund dalam Menekan Persebaran HIV/AIDS di Indonesia tahun 2003-2015 - Surya Merta, I Gede Agus Anggita; Sushanti, Sukma; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2018), 2018)
ABSTRACT Indonesia has undertaken various technical efforts to fight against HIV/AIDS including to raising global awareness for covering the shortage of funds incurred by the implementation of technical programs. The Global Fund as an international funding institution provides intensive largest funding assistance to Indonesia. However, this is not directly make Indonesia's success in suppressing the spread of HIV/AIDS which tends to increase every year. This study discusses more deeply about the factors that hinder the achievement of HIV/AIDS prevention programs in Indonesia. This research data is obtained from various sources such as scientific research, journals, and reports. In this study, factors that inhibit the success of suppressing the spread of HIV/AIDS in Indonesia are weak institutional and program governance systems, lack of involvement of affected communities in the formulation of programs, and access to HIV/AIDS services that are not integrated with services other general health. Keywords: The Global Fund, Internal Factors inhibiting Foreign Aid in Suppressing the Spread of HIV/AIDS in Indonesia, Dillemmas of Foreign Assistance.